Engineered liposomal nanoparticles and their medical applications - Syed Mahmood, .; Mohd Azmir, Arifin; Hilles, Ayah R. (Scrivener Publishing/Wiley & Sons Inc., 2025)
A liposome is a vesicle like a tiny bubble, which can be filled with drugs and used to deliver drugs for different diseases. The liposomes have been employed surface ligands for attaching small molecules, carbohydrates, vitamins, proteins, peptides, enzymes, and antibodies. These advanced liposomes possess higher stability, greater solubility, specific drug-targeting ability, and long circulating time. Liposomes also improve controlled distribution, drug solubility, and their capacity for surface modifications for targeted, prolonged, and sustained release. Liposomes are considered the most common nanocarriers used for various active hydrophilic and hydrophobic molecules due to their low immunogenicity, biocompatibility, and biodegradability. Many liposomal-based drug delivery systems are clinically approved to treat different diseases, like cancer and viral and fungal infections. Liposomes provide an established basis in industrial applications including the use of liposomes as adjuvants in vaccination, signal carriers and enhancers in medical diagnostics, solubilizing and supporting matrices for multiple ingredients, and penetrating enhancers in cosmetics. This chapter summarizes the types of liposome nanoparticles and engineered liposomal drug-delivery platforms, including PEGylated liposomes, ligand-targeted liposomes, and theranostic liposomes. In addition, this chapter discusses the medical applications of engineered liposomes.